Physical Simulation of Gas–Liquid Mass Transfer Behavior in Oxygen Bottom Blowing Copper Furnace - Zelei Zhang; Pin Shao; Shuyu Shi (Metals)
In order to improve the internal chemical reaction efficiency of oxygen bottom blowing copper smelting furnace, the efficient separation and flow control device and technology of matte and slag in oxygen bottom blowing copper smelting furnace were put forward. A physical model was established to investigate the effects of the insertion depth of the retaining wall, the horizontal distances, the gas flow rate, and the diameter of the deflector holes on the gas–liquid mass transfer behavior in the molten bath and the gas utilization rate. The results show that the gas–liquid mass transfer rate and the gas utilization rate will decrease with the increase in the depth when the insertion depth of the retaining wall is more than 0.054 m. The horizontal distance is 1.18 m, and the area of the whole reaction zone is suitable. The absence of diversion holes is conducive to smelting. The gas flow rate of 3.0 Nm3/h is beneficial to the gas–liquid mass transfer behavior and the gas utilization rate.